Pembelajaran gizi menggunakan media buku gizi braille dan peningkatan pengetahuan gizi seimbang siswa sekolah dasar penyandang tunanetra - Arum Sekar Pratiwi; Weni Kurdanti; Slamet Iskandar (PUINOVAKESMAS, 2021)
Nutrition problem in visually impaired children is similar with normal kid. The problem is caused by lack of knowledge and low application of balance nutrition in everyday life. Therefore, it’s important to educate visually impaired children on nutrition education with media that suit their characteristics. To investigate the effectiveness of nutrition education using the nutrition Braille book toward knowledge of visually impaired children. This research was quasi-experimental with pretest-posttest without control group design, conducted in SLB A YKAB Solo and SLB A ‘Aisyiyah Ponorogo. The intervention was education using the nutrition Braille book. Subjects were elementary students aged 9-13 years in SLB A YKAB Solo and SLB A ‘Aisyiyah Ponorogo with a total respondent of 14 students. Knowledge is measured using a questionnaire. Data were analyzed by paired sample t-test. Based on paired sample t-test output, the results show that there are significant differences in mean scores before and after nutritional education (p=0.000) with an increased rate of 47.7%. Nutritional education using the nutrition Braille book can increase knowledge of balanced nutrition in elementary students with visual impairment.